Play and social interaction in financial education activities in kindergarten - Conceição Tatiana Moreira Botelho; Cleci Teresinha Werner da Rosa; Luiz Marcelo Darroz (Amazônia, 2025)
The study identifies the need to promote spaces in kindergarten that provide opportunities to value skills, abilities and attitudes that recognize the importance of financial education from an early age. In this sense, the research question was expressed as follows: what is the pedagogical relevance of activities aimed at addressing financial education with children in kindergarten? The objective of the study is to analyze the didactic feasibility and the process of interaction provided to children in kindergarten, through a set of activities focused on financial education. To achieve this goal, a set of didactic activities focused on interaction and play were developed, which were applied in five meetings over the course of a week, with preschool children from a public school. The research is based on a qualitative approach, using data production through the researcher's records, materials produced by the children and video recordings. Data analysis is limited to three episodes, investigating, in each one, the didactic feasibility and the process of interaction provided in each activity. The results indicate children's involvement in the activities, their ability to understand the value of money and their awareness of the importance of saving to acquire things